Hubungan antara Pendidikan Kesehatan Mental dengan Penurunan Tingkat Stigma terhadap Orang dengan Gangguan Mental - Asriyanti Rosmalina (UIN Siber Syekh Nurjati Cirebon, 2025)
This research aims to analyze and empirically test the relationship between mental health education and a decrease in the level of social stigma towards People with Mental Disorders (ODGM). High stigma is a significant obstacle for ODGM in seeking professional help and social reintegration. The research design uses a quasi-experimental quantitative approach involving two groups: the intervention group that received a structured mental health education program (including psychoeducation on the etiology, symptoms, and treatment of mental disorders) and the control group. The research subject is a student from university X (N=100). Stigma measurement is done before (pre-test) and after (post-test) of the intervention using an Attitude Towards Mental Illness (ATMI) questionnaire that has been adapted. The research results showed a significant decrease in the stigma score of the intervention group (p < 0.05) compared to the control group. This result indicates that mental health education interventions have substantial effectiveness as a strategy to reduce discrimination and increase social acceptance of People with Mental Disorders.